Magmatic Ore Deposits 1969
DOI: 10.5382/mono.04.23
|View full text |Cite
|
Sign up to set email alerts
|

Phase Relations in the Cu-Fe-S, Cu-Ni-S, and Fe-Ni-S Systems

Abstract: The phase relations in the Cu-Fe-S, Fe-Ni-S, and Cu-Ni-S systems were investigated by silica-tube quenching, differential thermal analysis, and high-temperature X-ray powder diffraction experiments. In addition, portions of the Cu-Fe-S and Fe-Ni-S systems were studied by gold-tube quenching and differential thermal analysis experiments under high confining pressures. At elevated temperatures extensive liquid immiscibility fields span the sulfur-rich region of each of the three systems, whereas h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…11), are more consistent with their formation in a portion of the Fe-Ni-Cu-S system dominated by the early (850-900 °C) crystallization of the quaternary solid solution comprising the compositional range between hzss and iss solid solutions (Peregoedova and Ohnenstetter, 2002). Once cooling, this quaternary solid solution may increase its bulk Ni/Cu ratio breaking down to pentlandite from hzss at ∼760 °C and chalcopyrite (and/or bornite) from iss below 557 °C (Fleet and Pan, 1994;Kullerud et al, 1969;Peregoedova and Ohnenstetter, 2002), explaining the observed pn ± cp ± bn assemblages in the Tallante peridotites (Fig. 4).…”
Section: Fingerprinting the Origin Of Bms Included In Metasomatic Pyroxenementioning
confidence: 74%
See 2 more Smart Citations
“…11), are more consistent with their formation in a portion of the Fe-Ni-Cu-S system dominated by the early (850-900 °C) crystallization of the quaternary solid solution comprising the compositional range between hzss and iss solid solutions (Peregoedova and Ohnenstetter, 2002). Once cooling, this quaternary solid solution may increase its bulk Ni/Cu ratio breaking down to pentlandite from hzss at ∼760 °C and chalcopyrite (and/or bornite) from iss below 557 °C (Fleet and Pan, 1994;Kullerud et al, 1969;Peregoedova and Ohnenstetter, 2002), explaining the observed pn ± cp ± bn assemblages in the Tallante peridotites (Fig. 4).…”
Section: Fingerprinting the Origin Of Bms Included In Metasomatic Pyroxenementioning
confidence: 74%
“…4). At the temperature conditions (850-1050 °C) estimated for the equilibration of this set of mantle xenoliths (Hidas et al, 2016), phase relations in the Fe-Ni-Cu-S system predict that Fe-rich monosulfide solid solution (mss) should be the first solid to crystallize from sulfide melt droplets (Kullerud et al, 1969). If so, the fractionation of such sulfide melts must be governed by the sequential crystallization of monosulfide (mss) and/or intermediate (iss) [(Cu 1 ± x Fe 1 ± y )S 2 ] solid solutions (Ballhaus et al, 2001).…”
Section: Fingerprinting the Origin Of Bms Included In Metasomatic Pyroxenementioning
confidence: 99%
See 1 more Smart Citation
“…The elevated Sr/Y ratios of many intermediate rocks in the CTD (Figs. 3f and S3a), particularly of the Cu/Au ore-related stock/dikes, suggest that the parental mafic magmas of these rocks probably experienced major amphibole (± garnet) fractionation and only limited plagioclase (Kullerud et al 1969). The displacement of some data points outside the MSS field towards higher S contents is due to the relatively large uncertainty associated with S analyses by LA-ICP-MS. (Richards and Kerrich 2007).…”
Section: Petrogenesis and Fertility Of Early Cretaceous Magmatic Rocks In The Ctdmentioning
confidence: 97%
“…Sulfides are included into diamond as hightemperature monosulfide solid solution (Mss), exsolving to Fe-, Ni-, and Cu-rich end members during cooling associated with volcanic exhumation (Kullerud et al, 1969). This exsolution causes fractionation of major and trace elements within the inclusions (Richardson et al, 2001), and unless the inclusions can be extracted and studied in their entirety, this process limits the ability to extract accurate isotopic information for geochronology.…”
Section: Introductionmentioning
confidence: 99%